1992
DOI: 10.1139/b92-303
|View full text |Cite
|
Sign up to set email alerts
|

Effet des conditions de culture sur la mycorhization de l’Helianthemum guttatum par trois espèces de terfez des genres Terfezia et Tirmania d'Algérie

Abstract: Three species of edible desert truffles, Terfezia arenaria, Terfezia claveryi, and Tirmania pinoyi associated with Helianthemum guttatum in Algeria were examined in this study. The mycorrhizal synthesis between the three species of desert truffles and Helianthemum guttatum was carried out with two different methods: (i) under axenic conditions on perlite permeated by a nutritive solution, by inoculating the seedlings with mycelial fragments; (ii) under gnotoxenic conditions on natural substrates, by inoculatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 8 publications
2
37
0
1
Order By: Relevance
“…The morphology of the mycorrhizas formed in our experiments was similar to that of the ectendomycorrhizas described by Fortas and Chevalier (1992). Both the extramatricial and intercel- lular hyphae were moniliform or beadlike.…”
Section: Mycorrhizationsupporting
confidence: 83%
See 1 more Smart Citation
“…The morphology of the mycorrhizas formed in our experiments was similar to that of the ectendomycorrhizas described by Fortas and Chevalier (1992). Both the extramatricial and intercel- lular hyphae were moniliform or beadlike.…”
Section: Mycorrhizationsupporting
confidence: 83%
“…Using non-micropropagated plants of Helianthemum guttatum and a substrate of perlite watered with a nutrient solution, Fortas and Chevalier (1992) obtained mycorrhizas of Terfezia under axenic conditions. Roth-Bejerano et al (1990) also obtained mycorrhizas with seedlings of Helianthemum sessiliflorum and Terfezia leonis in a half-strength Hoagland's solution with agar and activated charcoal.…”
Section: Mycorrhizationmentioning
confidence: 99%
“…Most Terfezia species establish mycorrhizal symbiosis with plants from family Cistaceae, mainly with perennial and annual Helianthemum species (Dexheimer et al 1985, Fortas & Chevalier 1992, Gutiérrez et al 2003, and with trees from different phyla (Bordallo et al 2013, Díez et al 2002, Taylor et al 1995. These plants and their associated fungi play a major role in the maintenance of Mediterranean shrub lands and xerophytic grasslands, and thus in preventing erosion and desertification (Honrubia et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Superficially, they were white. When electronic microscopy was used, the spherical shape and smooth surface of ascospores showed that they were those of T. pinoyi (Maire) Malençon (Fortas and Chevalier, 1992) (Figure 2). Fruiting bodies were cleaned of soil and were air dried under the sun until constant weight.…”
Section: Methodsmentioning
confidence: 99%